Effects of 20-hydroxyecdysone and other hormones on egg development, and identification of a vitellin-binding protein in the ovary of the tick, Amblyomma hebraeum - Friesen, Kevin; Kaufman, Reuben (My University, 2004)
Partially fed adult female Amblyomma hebraeum ticks were injected with 20-hydroxyecdysone (20E; up to 43 μg/g body weight (bw)), juvenile hormone III (JH III; up to 100 μg/g bw), bovine insulin (up to 2000 mU/g bw), or triiodothyronine (up to 200 ng/g bw) in an attempt to stimulate vitellogenesis. Of these, only 20E stimulated synthesis and release of vitellogenin (Vg). Immunoblot analysis revealed that Vg-synthesis occurred in the fat body. However, consistent with earlier observations suggesting that a distinct signal may be required for Vg-uptake, there was no significant Vg-uptake by oocytes of partially fed, 20E-treated ticks. Because Vg-uptake commonly occurs via receptor-mediated endocytosis (i.e., a specific Vg-receptor), we attempted to identify a vitellin (Vt)-binding protein in ovaries of engorged female ticks. A single 86 kDa Vt-binding protein was identified, even under reducing conditions (2-mercaptoethanol), by a ligand-blotting technique. Sodium salt of suramin (5 mM) inhibited binding of Vt to the 86 kDa protein. However, this protein was also detected in ovaries from small partially fed ticks (50–100 mg), suggesting that the inability of 20E to stimulate Vg-uptake in partially fed ticks may not have been due to the absence of a Vg-receptor.
Keywords: ixodid ticks; amblyomma hebraeum; vitellogenesis; vitellogenin; vitellin; 20-hydroxyecdysone; juvenile hormone; vitellogenin-receptor; insulin; triiodothyronine (T3)